Exploring exercise-driven inhibition of pyroptosis: novel insights into treating diabetes mellitus and its complications - Li, Nan; Zhang, Liang; Wang, Xintang; Zhou, Yue; Gong, Lijing (Frontiers in Endocrinology, 2023)
Diabetes mellitus (DM) and its complications are important, worldwide public health issues, exerting detrimental effects on human health and diminishing both quality of life and lifespan. Pyroptosis, as a new form of programmed cell death, plays a critical role in DM and its complications. Exercise has been shown to be an effective treatment for improving insulin sensitivity or preventing DM. However, the molecular mechanisms underlying the effects of exercise on pyroptosis-related diseases remain elusive. In this review, we provided a comprehensive elucidation of the molecular mechanisms underlying pyroptosis and the potential mechanism of exercise in the treatment of DM and its complications through the modulation of anti-pyroptosis-associated inflammasome pathways. Based on the existing evidence, further investigation into the mechanisms by which exercise inhibits pyroptosis through the regulation of inflammasome pathways holds promising potential for expanding preventive and therapeutic strategies for DM and facilitating the development of novel therapeutic interventions.